A STUDY OF COOPERATIVE PRINCIPLES IN CONVERSATION OF TENANTS AT KAMPOENG INGGRIS PARE, KEDIRI - Lazulfa, Farhat Indana; Pamolango, Valantino A. (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
This research describes the study of Gricecooperative principles in conversations of tenants at KampoengInggris Pare, Kediri. This study aims at finding out if the conversations of the tenants meet Grice’s four maxims. From the analysis, it can be concluded that every conversation of tenants at Kampoeng English Pare Kediri meets Grice cooperative principles.The results of this study also show that the conversations in KampoengInggrisPare, Kediri adhere to the maxim of relevance. The speech act shows the attempt to contribute relevant information. In the conversation, the tenants also have to speak their mind to use a clear and coherent narrative. The speech acts of tenantsindicate that the implementation of the principle of cooperation adheres to the maxim of manner.Kata Kunci: cooperative principles, tenant, Kampoeng Inggris Pare